Implementação de software de controle financeiro em uma microempresa do ramo de panificação de Sant’Ana do Livramento-RS - Martins, Wanderson Gonçalves (2017)
Finance in organizations must be among the main issues to be controlled and analyzed within a business context, and the manager has tools to assist in the diagnosis of financial matters and in decision-making. Based on this premise, the purpose of this article is to include the financial control software for MEI's and Microenterprises called AcompanhaME® developed by SEBRAE-DF. Through an action research carried out in a bakery characterized as a microenterprise of the city of Sant'Ana do Livramento-RS, it was possible to implement the use of the tool during the month of July 2017 in order to show how the implementation would occur with respect the proposal of improvement of the financial control of the company and the processes that compose it, have seen the empirical way that was practiced, and how would the organization manager use a tool never used by it. In the course of the study, the numbers collected and organized by the software were presented and debated, diagnosing a better organization and control in the company's finances, which made possible new decisions within the company, such as reorganization of the bank payment period together to suppliers. Another point evaluated was the satisfactory operation of the software by the owner of the organization, because due to a brief training before the beginning of the study it was possible to transmit to it the simplified operation of the software, contemplating its functionalities in order to promote a reduction in difficulty during the study period.